Proficiency and Error of English Final Consonant Cluster Pronunciation Produced by Sundanese Students - Irawan, Yusup; Pratama, Dyta Ayunda; Kurnia, Nia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to examine Sundanese students’ proficiency and errors in performing final consonant clusters in English. The research used a qualitative approach. The participants in this research were 40 college students. Their mother tongue was Sundanese. The data were recordings, which were collected through a pronunciation test of the target clusters in a provided word list. A perceptual approach was applied to analyze the data recordings. The results of this research found that the Sundanese students were not satisfactory when performing consonant clusters in English. They were only at intermediate levels. Omissions were major errors made by the students. The Sundanese students typically omitted the last consonant for -CC and the middle consonant for -CCC and -CCCC. In addition, the Sundanese students’ semester and their English grades affected the Sundanese students’ proficiency. It seemed that the differences in clusters’ phonological structure between English and Sundanese and unfamiliar sounds contributed to the errors. This research suggests that teachers perform explicit instruction to improve students’ cluster proficiency and enhance students’ phonetic knowledge of English clusters. Accurate pronunciation is an important factor affecting communication intelligibility.